Status prawny prowincji mezyjskich w okresie wojen markomańskich - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2020)
In 1962, Anthony R. Birley advanced a remarkable thesis, claiming that the rank of the Roman province of Upper Moesia (Moesia superior) was temporarily reduced from consular to praetorian. To support the assertion, he cited the fact that one of the two legions stationed in the province left it for a period of time; this automatically entailed a revision of its status, which was thus downgraded. A province with one legion was governed by a former praetor, whereas a province with two or more legions was administered by a former consul (vir consularis). A.R. Birley drew on the account in SHA vita Marci 22.9, which states that Marcus Aurelius changed – pro belli necessitate – the status of several provinces, as well as on two inscriptions (CIL III 1566; XIII6806), which contained an unorthodox record of senatorial careers. Both inscriptions mention Upper Moesia. A.R. Birley’s proposition was widely accepted by researchers, though critical views were also expressed. Nonetheless, its impact was so effective that it was subsequently argued that the mechanism should be presumed to have applied to Lower Moesia (Moesia inferior) as well. Still, a thorough analysis of all available sources permits one to conclude that the view is erroneous and altogether unfounded. In fact, its represents an outcome of a puristic application of the prosopographic method, which in this case proved a fundamental mistake.